Portret trumienny - Piwowarski, Krystian, 1956- (Katowice : Wydawnictwo "Slask", 1989)
A selection of short stories by a contemporary author.
Gosc -- Oddzial -- Zenon i Zofia -- Bitwa -- Pan Ciswicki.
Short stories.
Keywords: short stories, Polish